Event handling for distributed real-time cyber-physical systems - Singh, Jaipal; Hussain, Omar; Chang, Elizabeth; Dillon, Tharam (Curran Associates Inc., 2012)
Cyber-Physical Systems (CPS) provides a smart infrastructure connecting abstract computational artifacts with the physical world. This paper presents some challenges for developing distributed real-time Cyber-Physical Systems. The focus is on one particular challenge, namely event modelling in distributed real-time CPS. A Web-of-Things based CPS framework for event handling and processing is proposed. To illustrate the application of the proposed framework, a case study for achieving demand response in a smart home is provided.